Respuesta :
Use foil (first, outer, inner, last)
First terms: 3x * 6x = 18x²
Outer terms: 3x * 1 = 3x
Inner terms: -2 * 6x = -12x
Last terms: -2 * 1 = -2
Put all that together to get 18x² + 3x - 12x - 2
3x and -12x can be combined because they're like terms; 3x - 12x = -9x
So the final product is 18x² - 9x - 2
Answer:
18x² - 9x - 2
Step-by-step explanation:
Each term in the second factor is multiplied by each term in the first factor, that is
3x(6x + 1) - 2(6x + 1) ← distribute both parenthesis
= 18x² + 3x - 12x - 2 ← collect like terms
= 18x² - 9x - 2